Maintaining Local Wisdom For Food Security: The Ethnobotanical Potential Of Repong Damar In Krui Selatan Sub-District, Pesisir Barat Regency, Lampung, LAMPUNG - Sa’adah, Miftahus; Duryat; Hari Kaskoyo; Sugeng P. Harianto (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Ethnobotanical practices represent a form of local wisdom that is still preserved by the Repong Damar community in Krui Selatan, Pesisir Barat Regency, Lampung, primarily utilized as a source of traditional food. This study aims to identify ethnobotanical food practices applied by the Repong Damar community in Krui Selatan Sub-district, to inventory the plant species utilized as food sources, and to analyze their forms of utilization. The research employed an ethnographic approach through semi-structured interviews, field observations, and documentation as supporting data. The results showed that ethnobotanical food practices are still actively carried out by the Repong Damar community. A total of 13 main species were identified, including Parkia speciosa, Lansium speciosa, Durio zibethinus, Archidendron pauciflorum, Miconia crenata, Litsia sp., Gnetum gnemon, Garcinia mangostana L., Persea americana, Piper nigrum, Syzygiumaromatica, Mangifera indica, Archidendron bubalinum. The forms of utilization include being consumed raw, cooked as vegetables, processed into emping, used as cooking spices, and as food aromatics. These findings indicate that ethnobotanical food practices play an important role not only in fulfilling daily food needs but also in preserving local wisdom and supporting food security at the local level.